Poor kidney graft survival in anorexia nervosa patients - Geneviève, Magalie; Sartorius, Albane; Giral, Magali; Janbon, Bénédicte; Merville, Pierre; Legendre, Christophe; Combe, Christian; Moreau, Karine (Eating and weight disorders, 2021)
Background Anorexia nervosa is a condition associated with poor outcomes in a variety of circumstances such as recurrence of eating disorders, psychiatric disorders, and organ damage. Objective In the present study, we first sought to determine the 5-year kidney graft survival in patients with anorexia nervosa and then to evaluate the BMI course and medical complications. Methods In this multicenter, retrospective, case–control study, we analyzed the impact of anorexia nervosa on graft outcomes compared to transplant recipients with low or normal BMI. Results We enrolled 137 women in this study: 19 with anorexia nervosa, 59 with low BMI (BMI < 18.5 kg/m 2 ), and 59 with normal BMI (18.5–24.9 kg/m 2 ). Anorexia nervosa was significantly associated with lower graft survival compared to either of the other groups (hazard ratio 5.5 [95% CI 3.4–8.9], p = 0.005); there was no difference in graft survival between patients with low or normal BMI. Cardiovascular complications were more frequent in the anorexia nervosa group (37%) than in patients with low (6%) or normal BMI (7%) ( p = 0.001). Conclusion We conclude that patients with anorexia nervosa should be considered a high-risk group. Level of evidence Level III, evidence obtained from well-designed cohort or case–control analytic studies.